2020
DOI: 10.1021/acs.jced.0c00769
|View full text |Cite
|
Sign up to set email alerts
|

Relative Permittivity of Stockmayer-Type Model Fluids from MD Simulations and COFFEE

Abstract: The relative permittivity is a property that depends on the orientation structure of a fluid. Thus, using state-of-the-art equations of state it can be modeled only when using high level techniques, such as nonprimitive models. This is a drawback, especially when electrolytes are present: when using a primitive model, an auxiliary model for the relative permittivity must be introduced. Here, we pursue a different approach to predict the relative permittivity. The recently developed 'Co-Oriented Fluid Functiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…These new data are used to reparametrize the expression for the near field of COFFEE for pure fluids. As proposed, e.g., in the perturbation theory of Tani et al and confirmed quantitatively by MD simulations of Kohns et al, , the relative permittivity of ST fluids as well as that of real substances may be expressed as a univariate function of the dipole strength where μ* is the dipole moment, ρ* the number density, and T * the temperature. It is found that the same holds true for the correction factor I μμ NF as introduced in COFFEE for pure fluids .…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…These new data are used to reparametrize the expression for the near field of COFFEE for pure fluids. As proposed, e.g., in the perturbation theory of Tani et al and confirmed quantitatively by MD simulations of Kohns et al, , the relative permittivity of ST fluids as well as that of real substances may be expressed as a univariate function of the dipole strength where μ* is the dipole moment, ρ* the number density, and T * the temperature. It is found that the same holds true for the correction factor I μμ NF as introduced in COFFEE for pure fluids .…”
Section: Methodsmentioning
confidence: 70%
“…These new data are used to reparametrize the expression for the near field of COFFEE for pure fluids. As proposed, e.g., in the perturbation theory of Tani et al 51 and confirmed quantitatively by MD simulations of Kohns et al, 39,40 the relative permittivity of ST fluids as well as that of real substances may be expressed as a univariate function of the dipole strength…”
Section: Journal Of Chemical and Engineering Datamentioning
confidence: 69%
See 1 more Smart Citation
“…Distinguishable angles and vectors in the coordinate system for the calculation of the ODF. Reproduced from ref . Copyright 2020 American Chemical Society.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, when these parameters are fit to other pure-component data, e.g., for the vapor–liquid equilibrium commonly employed in EOS modeling, the relative permittivity of the fluid at any state point can be obtained in a strictly predictive manner. COFFEE has been used in recent work to model the relative permittivity of pure Stockmayer fluids, which consist of a Lennard-Jones center with a superimposed point dipole. COFFEE has been recently extended to mixtures, and hence, it now offers the possibility to also study relative permittivities of mixtures …”
Section: Introductionmentioning
confidence: 99%